Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Vamos resolver o problema passo a passo, considerando as informações fornecidas:
1. Temos que [tex]\(\log_a b = -2\)[/tex] e [tex]\(a \cdot b = 3\)[/tex].
2. A equação [tex]\(\log_a b = -2\)[/tex] pode ser reescrita na forma exponencial:
[tex]\[ b = a^{-2} \][/tex]
Isso nos diz que [tex]\(b\)[/tex] é igual ao inverso do quadrado de [tex]\(a\)[/tex].
3. Substituímos [tex]\(b = a^{-2}\)[/tex] na equação [tex]\(a \cdot b = 3\)[/tex]:
[tex]\[ a \cdot a^{-2} = 3 \][/tex]
4. Simplificando a equação:
[tex]\[ a^{-1} = 3 \][/tex]
Isso implica que:
[tex]\[ a = \frac{1}{3} \][/tex]
5. Agora, substituímos [tex]\(a = \frac{1}{3}\)[/tex] na forma exponencial para encontrar [tex]\(b\)[/tex]:
[tex]\[ b = \left(\frac{1}{3}\right)^{-2} \][/tex]
Lembrando que [tex]\(\left(\frac{1}{3}\right)^{-2} = \left(\frac{3}{1}\right)^2 = 9\)[/tex], temos:
[tex]\[ b = 9 \][/tex]
6. Agora temos [tex]\(a = \frac{1}{3}\)[/tex] e [tex]\(b = 9\)[/tex].
7. Finalmente, calculamos [tex]\(b - a\)[/tex]:
[tex]\[ b - a = 9 - \frac{1}{3} \][/tex]
Para subtrair frações, encontramos um denominador comum:
[tex]\[ 9 - \frac{1}{3} = \frac{27}{3} - \frac{1}{3} = \frac{27 - 1}{3} = \frac{26}{3} \][/tex]
Portanto, o valor de [tex]\(b - a\)[/tex] é [tex]\(\frac{26}{3}\)[/tex].
A resposta correta é:
d) [tex]\(\frac{26}{3}\)[/tex]
1. Temos que [tex]\(\log_a b = -2\)[/tex] e [tex]\(a \cdot b = 3\)[/tex].
2. A equação [tex]\(\log_a b = -2\)[/tex] pode ser reescrita na forma exponencial:
[tex]\[ b = a^{-2} \][/tex]
Isso nos diz que [tex]\(b\)[/tex] é igual ao inverso do quadrado de [tex]\(a\)[/tex].
3. Substituímos [tex]\(b = a^{-2}\)[/tex] na equação [tex]\(a \cdot b = 3\)[/tex]:
[tex]\[ a \cdot a^{-2} = 3 \][/tex]
4. Simplificando a equação:
[tex]\[ a^{-1} = 3 \][/tex]
Isso implica que:
[tex]\[ a = \frac{1}{3} \][/tex]
5. Agora, substituímos [tex]\(a = \frac{1}{3}\)[/tex] na forma exponencial para encontrar [tex]\(b\)[/tex]:
[tex]\[ b = \left(\frac{1}{3}\right)^{-2} \][/tex]
Lembrando que [tex]\(\left(\frac{1}{3}\right)^{-2} = \left(\frac{3}{1}\right)^2 = 9\)[/tex], temos:
[tex]\[ b = 9 \][/tex]
6. Agora temos [tex]\(a = \frac{1}{3}\)[/tex] e [tex]\(b = 9\)[/tex].
7. Finalmente, calculamos [tex]\(b - a\)[/tex]:
[tex]\[ b - a = 9 - \frac{1}{3} \][/tex]
Para subtrair frações, encontramos um denominador comum:
[tex]\[ 9 - \frac{1}{3} = \frac{27}{3} - \frac{1}{3} = \frac{27 - 1}{3} = \frac{26}{3} \][/tex]
Portanto, o valor de [tex]\(b - a\)[/tex] é [tex]\(\frac{26}{3}\)[/tex].
A resposta correta é:
d) [tex]\(\frac{26}{3}\)[/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.